CRITICAL ANALYSIS OF THE USE OF TECHNOLOGY IN DENTAL CARE - SULIMAN MUQHIM ALMUQHIM, MOHAMMED ZABEN BAS ALSHAMMARI, AYEDH BAKHIT OSHISH AL GHAMDI, MOHAMMED ALI MUIDH ALRIZQI, AHMAD ABDULMOHSEN ALMAREK, MOHAMMED AQEEL ALSHAMMARI, ABDULLAH HAMEED ALSHAMMARI, YAZEED MOHAMMED TURKISTANI (Chelonian Research Foundation, 2022)
Technology has been so integrated into dentistry practice that it has profoundly changed the field. Dental care has been provided with new solutions that are in use for diagnosis, treatment, and interfacing with patients. This paper critically focuses on the technology usage for dentistry operations, highlighting the impact on clinical results, patient satisfaction, and practice efficiency. A wide-ranging literature review will be conducted, with the aim of drawing conclusions regarding the kinds of technology utilized in modern dentistry, their benefits and flaws, and the implications all of these have for the dental profession. The study shows that technology is not only for better diagnostics and guidance of treatments but also for effectively engaging with patients. The discussion details the challenges facing the adoption of these digital innovations, such as resource cost, technical ability, and ethical implications, but puts forward recommendations that ask for sustained investments in novel developments and the training of dental personnel to facilitate the optimal use of technology for the enhancement of oral health. Keywords: technology, dental diagnosis, dental treatment, patient organization, and innovative approach in the future.